Proceedings of the 1st International Scientific Conference "Teaching Methods for Economics and Business Sciences", 8 May 2017, Maribor, Slovenia (University of Maribor Press, 2017)
Teaching is a challenging but also a rewarding profession. It is underpinned by one key question: how do we build a good teaching and learning environment so that our students can acquire professional competences which will enable them to be successful in today’s global business environment. These proceedings include the papers presented at the 1st International Scientific Conference »Teaching Methods for Economics and Business Sciences« held on 8 May 2017 at the University of Maribor, Faculty of Economics and Business. The papers address students’ learning outcomes, the development and measurement of students’ professional and transversal competences and skills, creative teaching and learning techniques such as brainstorming and creative problem solving, active learning and collaborative learning, students’ self-assessment of their learning, experiential learning and lifelong learning, practical teaching methods such as business simulations, action-based learning and knowledge integration, innovations and sustainability of different teaching methods, non-formal learning and teaching activities for vocational competences development, ethical aspects of creating a good student environment, capacity building, students’ learning styles, teaching styles, students’ creativeness, and, last but not least, students’ academic success and their personal wellbeing. These papers provide valuable insights into academic teaching practice and contribute to the answer to the above question.